'Dracarys' for all: TV series and experiential learning. Issue 2 (April 2023) - Biehl, Brigitte
Film has been widely used for management learning, mostly with a focus on the story rather than on the film experience. This study draws on arts-based learning literature, film studies and data from learning interactions, and develops a taxonomy of experiential learning with film as a specific art form and emotional medium. The taxonomy includes three elements: making a film experience, processing the experience and cultural aesthetic reflexivity. This study provides process steps and teaching strategies to help move management learners along in the process towards specific learning outcomes. It introduces a film analysis tool as a method that can be used to overcome aesthetic muteness when reflecting on the film experience. The acclaimed and contested TV series Game of Thrones serves as a point of reference, and examples feature the female leader Daenerys Targaryen. The approach is transferable across films and TV series to integrate knowing, experience and emotions and to use popular culture's critical potential for management learning.